Human quadrupedalism is not an epiphenomenon caused by neurodevelopmental malformation and ataxia - Karaca, Sibel; Tan, Meliha; Tan, Uner (Frontiers in Neurology, 2012)
Two cases of individuals with quadrupedal locomotion (QL) were presented. In both cases the brains and cognitive functions were normal and no neurological deficits were seen, except for a paralyzed leg in case 2. It was suggested that human QL (i) should not be considered as an epiphenomenon caused by neurodevelopmental malformation and ataxia, but (ii) may be considered as a re-emergence of the ancestral diagonal QL, and (iii) it may spontaneously emerge in humans with entirely normal brains, by taking advantage of neural networks such as central pattern generators that have been preserved for about 400 million years.